Specific vs Unspecific Smoke-Free Regulation: Which One is More Effective? - Hesti Retno Budi Arini; Rumayya Rumayya; Muhammad Syaikh Rohman; Nur Annisa Fauziyah; Oktavian Denta Eko Antoro (Faculty of Public Health, Hasanuddin University, Makassar, 2023)
Tobacco kills up to half of its users, and smoking prevalence and tobacco exposure among Indonesian youth are increasing. A comprehensive ban on Tobacco Advertising, Promotion, and Sponsorship (TAPS) is a recommended tobacco control measure. Thus, this study aimed to analyze and compare political economy factors that contribute to the effectiveness of the TAPS ban implementation in Surabaya and Kulon Progo. In-depth interviews and a focus group discussion were conducted, recorded, transcribed, then analyzed using thematic analysis. We find that the role of local government was pivotal in creating and implementing regulations for tobacco control, while the leaders’ will and capability were also essential. However, the COVID-19 pandemic had limited all tobacco control measures in both studied districts. Furthermore, the lack of political will and low support from the political parties are the several factors hindering tobacco control measures at the district level, including TAPS ban enforcement. We also find that there is a need to strengthen the understanding of local government, society, and other related stakeholders toward the urgency of the TAPS ban. Further studies calculating the impact of the total TAPS ban on local revenue and the potential benefit of a total TAPS ban are urgently needed for advocating total TAPS ban implementation in a broader scope of the country.